Tanggung Jawab Etis Penggunaan Artificial Intelligence Di Tanah Pendidikan: Formulasi Paradigma Baru Untuk Teknologi Otonom - Oktaviani Putri Dita; Radittya Mahasputra Antara; Agung Winarno (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
This study examines the application of Immanuel Kant's ethical principles in the use of autonomous technology based on Artificial Intelligence (AI) in the academic domain. AI technology has significantly impacted academic efficiency and innovation but has also raised serious ethical challenges, such as algorithmic bias, dependency on technology, and threats to privacy and transparency. Using a Kantian ethical approach, this research identifies key issues and proposes an ethical framework that places justice, transparency, and respect for human dignity at the core of the design and implementation of autonomous technologies. The findings indicate that algorithmic bias can exacerbate academic inequities, while excessive reliance on AI risks diminishing the critical and creative capabilities of academics. Additionally, privacy and accountability in the management of academic data emerge as major concerns requiring ethically grounded policy interventions. This study also highlights the need for a new paradigm ensuring that autonomous technologies uphold humanistic values in academic settings, such as inclusivity, intellectual autonomy, and justice.